ON THE PROSPECTS OF TAX INCENTIVES FOR INVESTMENTS IN BONDS - A. S. Solomentsev (Вестник университета)
Russian economy is in dire need of “long” money, the source of which may be the population’s investments in securities market instruments. Bonds seem to be a real alternative to bank deposits and an optimal investment tool from a position of risk and return. Taxation system of investment incomes is one of the key problems hindering the investment activity of the population. Sound tax policy will not only contribute to a change in the investment priorities of Russian citizens but will also lead to the development of financial markets and exchange infrastructure.Changes to the tax system, as well as an assessment of the benefits for the investor and the budget have been proposed in the article.